Technological means of communication and collaboration in archives and records management - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2004)
This study explores the international collaboration efforts of archivists and records managers starting with the hypothesis that Internet technologies have had a significant impact on both national and international communication for this previously conservative group. The use and importance of mailing lists for this purpose is studied in detail. A quantitative analysis looks globally at the numbers of lists in these fields and the numbers of subscribers. A qualitative analysis of list content is also described. The study finds that archivists and records managers have now created more than 140 mailing lists related to their profession and have been contributing to these lists actively. It also 'estimates' that about half of the profession follows a list relating to their work and that archivists seem to like lists more than records managers do. The study concludes that mailing lists can be seen as a virtual college binding these groups together to develop the field.
Keywords: archives administration; records management; Internet; mailing lists; forums